FORMATION OF MARKETING-ORIENTED APPROACH TO PROVIDING INNOVATIVE PRODUCTS OF INDUSTRIAL ENTERPRISE - Yu. Nikolaenko; R. Lavrov (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu, 2019)
In the article the questions of marketing support of innovations of domestic industrial enterprises in the conditions of international economic relations are considered. The features of marketing of innovations are justified; the tasks of marketing of innovations at different stages of its implementation are defined; sequencing of marketing of innovations is suggested; the stages of the process of perception of innovations by different groups of consumers are investigated.